Facts, values, and norms : - Railton, Peter Albert (Cambridge University Press, 2003)
We struggle daily with the notions of why we do what we do and of assigning values to our actions, although it seems possible through experience to gain knowledge and understanding of such matters. In contrast to the world of facts, values and morality seem insecure, easily influenced by illusion or ideology. How can objectivity and accuracy be applied to values and morality? Peter Railton's study reveals how a naturalistically informed view of the world might incorporate objective values and moral knowledge